PHONOLOGY: EXAMINING THE SOUND SYSTEM FROM AN EDUCATIONAL PERSPECTIVE - Nazwa Atalia Zahra; Rodiatul Audiyah Lubis; Prita Anggina Sari Siregar; Aghna Ilmi Parinduri; Yani Lubis (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to explain and find out how to examine the sound system from an educational perspective. This research is literature review research. Based on the results of the discussion, it can be concluded that the exploration of phonology in the realm of education reveals its multifaceted significance in language teaching and learning. Through a thorough examination of phonological concepts, educators gain insight into various aspects of language acquisition, literacy development, language teaching, and remediation strategies for language learning difficulties. Phonology serves as a foundational element in early literacy acquisition, language instruction, and language assessment, contributing to the holistic development of learners' language skills. By recognizing the pivotal role of phonology and integrating its principles into educational practices, educators can create supportive learning environments that cater to diverse learners' needs and promote their language proficiency and academic success. Thus, phonology emerges as a vital component in shaping effective language education policies and practices worldwide.